Can the Kenyan Jua Kali Mechanic be Trusted in Servicing the New Technology Rich Vehicles? - Wanyeki , Paul Machocho; Kitainge , Kisilu; Ferej , Ahmed (African Journal of Education,Science and Technology (AJEST), 2017)
Mechanics in automotive garages need to keep pace with the ever evolving technological changes in the industry in order to provide relevant service to their clients. The formal garage mechanics have their training provided by vehicle suppliers on every critical technological innovation introduced in their automobiles. But the Jua Kali mechanics on the other hand do not have this symbiotic connection with suppliers. This paper tries to answer the question: can the jua kali mechanic be trusted in servicing the new technology rich vehicles? The study used a descriptive survey research design. The study population consisted of Jua Kali practitioners who deal with repairs and servicing of automobiles within Eldoret town. Data was analyzed using the statistical package for social sciences (SPSS) software and content analysis techniques. The study found that the Jua Kali mechanics cannot be trusted in handling the new technology rich vehicle as they mostly relied on trial and error which more often than not leads to more damages.